Non-aqueous electrolyte secondary battery
By using lithium-containing composite oxides without Co or extremely low Co content and adding chain carboxylic acid ester and cyclic compounds to the electrolyte, the problem of reducing circulation characteristics in the prior art is solved, and high capacity and long Non-aqueous electrolyte secondary battery with lifespan.
Patent Information
- Application Number
- CN202080086268.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-10-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-10-13
AI Technical Summary
In the prior art, when lithium-containing composite oxide is used as the positive electrode active material, the cycle characteristics are actually reduced, especially in the electrolyte with chain carboxylic acid ester added, the capacity maintenance rate decreases with the increase of charge and discharge cycle.
The lithium-containing composite oxide without Co or extremely low Co content is used as the positive electrode active material, and a chain carboxylic acid ester with a carbon number of 2 to 4 and a cyclic compound having a cyclic structure are added to the electrolyte solution, such as 1 ,4-dioxane.
It realizes a nonaqueous electrolyte secondary battery with low cost manufacturing and excellent long-term circulation characteristics, which can take into account both high capacity and long life.
Smart Images

Figure CN114830395B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Secondary batteries, especially lithium-ion secondary batteries, have high voltage and high energy density, and therefore are expected to be used as power sources for small-sized civilian applications, power storage devices, and electric vehicles. In the process of seeking to extend the life of batteries, a solution has been proposed to use carboxylic acid ester compounds as solvents for electrolytes to improve cycle characteristics (Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2004-172120 Summary of the invention
[0006] As the positive electrode active material of lithium ion secondary batteries, composite oxides containing lithium and metals (particularly transition metals) are used. As composite oxides containing lithium and transition metals, lithium cobalt oxide (LiCoO 2 ).
[0007] On the other hand, in recent years, due to the rising cobalt prices accompanied by the increase in demand, it is desired to use a positive electrode active material that does not contain Co as much as possible. In this regard, attempts have been made to use lithium-containing composite oxides in which the content of Co is reduced by replacing part of the metal constituting the composite oxide with other metal elements. For example, attempts have been made to use lithium-containing composite oxides (NCAM) obtained by replacing part of Co in lithium cobalt oxide with Ni, Al and / or Mn.
[0008] In a battery in which the composite oxide NCAM is used as a positive electrode and an ester compound is added to an electrolyte, the cycle characteristics may be reduced.
[0009] One embodiment of the present disclosure relates to a nonaqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode contains a composite oxide, the composite oxide containing lithium as a first metal and a second metal X other than lithium, wherein the second metal X in the composite oxide contains Ni, Al, and Mn, the second metal X does not contain Co, or the atomic ratio Co / X of Co in the second metal X is not more than 0.02, and the electrolyte contains: a chain carboxylate having 2 to 4 carbon atoms, and a cyclic compound having a ring structure consisting of 2 oxygen atoms and 3 to 5 carbon atoms.
[0010] According to the present disclosure, a nonaqueous electrolyte secondary battery can be realized which can be manufactured at low cost and has excellent long-term cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a schematic perspective view in which a part of the nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is cut away. DETAILED DESCRIPTION
[0012] The non-aqueous electrolyte secondary battery of the embodiment of the present disclosure has: a positive electrode, a negative electrode and an electrolyte, the positive electrode contains a composite oxide, the composite oxide contains lithium as a first metal and a second metal X other than lithium. In the composite oxide, the second metal X contains Ni, Al and Mn. On the other hand, the second metal X does not contain Co, or the atomic ratio Co / X of Co in the second metal X is less than 0.02. The electrolyte contains: a chain carboxylic acid ester having 2 to 4 carbon atoms, and a cyclic compound having a ring structure composed of 2 oxygen atoms and 3 to 5 carbon atoms.
[0013] The above-mentioned chain carboxylic acid ester is included in the solvent of the electrolyte, thereby having the effect of improving the cycle characteristics. Among them, the viscosity of the electrolyte containing methyl acetate (MA) is low, so the electrolyte is easy to spread over the surface of the positive and negative electrode active materials, and the unevenness of the charge and discharge reactions at the positive and negative electrodes can be suppressed. As a result, the improvement effect of the cycle characteristics is high. In particular, even if the coating amount of the positive and negative electrode active materials is increased for high energy density, or the thickness of the active material layer is formed thicker, the electrolyte can also spread to the depth of the collector side of the active material layer. As a result, it is easy to take into account both high capacity and long life.
[0014] However, when the positive electrode active material uses a lithium-transition metal composite oxide containing Mn, the cycle characteristics are sometimes reduced by including the above-mentioned chain carboxylate in the electrolyte. As a reason for this, Mn is dissolved in the electrolyte with the oxidation or reduction of the chain carboxylate, and the possibility of the composite oxide becoming (deactivated) into a crystal structure that is difficult to reversibly absorb and release lithium ions is considered. As a result, it is believed that the capacity retention rate decreases as the charge and discharge cycle passes.
[0015] Generally, carboxylates are easily oxidized and also easily reduced. Among them, methyl acetate is easily oxidized and reduced in the battery. On the other hand, it is known that Mn is easily dissolved in the electrolyte. In the battery, the chain carboxylates exist in both an oxidized state and a reduced state, and can accept electrons from the positive and negative electrode active materials or give electrons to the positive and negative electrode active materials, thereby being able to change reversibly.
[0016] If the oxidized chain carboxylate reaches the vicinity of the positive electrode surface, it takes electrons from the positive electrode active material, and it is believed that a reaction that oxidizes the positive electrode active material sometimes occurs. At this time, if it is in a discharged state, the usual charging reaction of lithium ions being deintercalated from the positive electrode active material can be induced by the oxidized carboxylate. However, in a fully charged state or a state close to it, there is basically no lithium that can be deintercalated in the positive electrode active material, and therefore, a reaction of Mn dissolving instead of lithium can be induced. As a result, it is believed that the capacity retention rate is reduced.
[0017] The cyclic compound has the effect of inhibiting the reaction of the (oxidized or reduced) chain carboxylic acid ester at the positive electrode surface. It is believed that the cyclic compound is adsorbed on the surface of the positive electrode material to form a protective layer that hinders the reaction of the (oxidized or reduced) chain carboxylic acid ester at the positive electrode surface (for example, the oxidation or reduction reaction of the composite oxide). As a result, it is speculated that the deactivation of the positive electrode active material is inhibited, and the reduction in capacity can also be inhibited. That is, the capacity retention rate is improved when the battery charge and discharge cycle is repeated for a long time.
[0018] As mentioned above, the cyclic compound has a ring structure consisting of 2 oxygen atoms and 3 to 5 carbon atoms. That is, the cyclic compound has the following ring structure: a five-membered ring structure consisting of 2 oxygen atoms and 3 carbon atoms, a six-membered ring structure consisting of 2 oxygen atoms and 4 carbon atoms, or a seven-membered ring structure consisting of 2 oxygen atoms and 5 carbon atoms. The cyclic compound can be a derivative in which the hydrogen atoms bonded to the carbon atoms constituting the ring structure are substituted by other functional groups, such as alkyl groups such as methyl and ethyl or aromatic hydrocarbon groups such as benzyl. The cyclic compound can also be a dioxane having a six-membered ring structure.
[0019] As dioxanes, 1,2-dioxane, 1,3-dioxane, and 1,4-dioxane may be used. Among them, 1,4-dioxane is preferred. As dioxanes, 2-benzyl-1,3-dioxane may be used. It is believed that the protective layer derived from dioxane can maintain a stable structure even at high temperatures by coordinating lithium ions in the oxygen atoms in the dioxane.
[0020] Examples of other cyclic compounds include 1,3-dioxolane and 4-methyl-1,3-dioxolane having a five-membered ring structure.
[0021] The content of the cyclic compound in the electrolyte solution may be 0.5% by mass or more relative to the mass of the electrolyte solution, thereby achieving a significant improvement in the capacity retention rate.
[0022] The content of the cyclic compound in the electrolyte can be, for example, 5% by mass or less relative to the mass of the electrolyte. By making the cyclic compound contained in the electrolyte 5% by mass or less, an increase in the resistance of the positive electrode surface caused by the protective layer formed by the cyclic compound is suppressed. The content of the cyclic compound in the electrolyte can be 2% by mass or less, and can be 1.5% by mass or less.
[0023] The cyclic compound is consumed by the repetition of charge-discharge cycles. In the case of repeatedly charging and discharging the battery over a long period, in order to continue the effect of the cyclic compound, it is also necessary to make the electrolyte before injecting it into the battery or the electrolyte recovered from the battery from the initial use contain a sufficient amount of the above cyclic compound. The electrolyte recovered from the battery from the initial use only needs to contain, for example, 0.02% by mass or more of the cyclic compound relative to the mass of the electrolyte, and can be 0.1% by mass or more.
[0024] When the cyclic compound is consumed, as a result, a film (protective layer) derived from the cyclic compound is formed at least on the positive electrode surface. Assuming that the cyclic compound cannot be detected in the electrolyte in the battery, for the case where at least the positive electrode has a film derived from the cyclic compound on its surface, this embodiment is not included in the present invention.
[0025] The content of the cyclic compound in the electrolyte can be measured, for example, by using gas chromatography-mass spectrometry (GC-MS), nuclear magnetic resonance (NMR), ion chromatography, etc. for the electrolyte.
[0026] As the positive electrode active material, a composite oxide containing lithium as the first metal and a second metal X other than lithium is used. Specifically, the composite oxide can contain, for example, Li a Ni 1-x-y-z Co x Mn y M 1 z O 2 (where 0 ≤ x ≤ 0.02, 0 < y ≤ 0.05, 0 < z ≤ 0.1) lithium-containing composite oxide. M 1 can contain Al. Co may not be contained in the second metal X (that is, x = 0 may be possible). When Co is contained, the atomic ratio of Co in the second metal X is 0.02 or less (x ≤ 0.02). It should be noted that the lithium ratio a varies depending on charge and discharge, but in the fully discharged state or the initial state just after the active material is produced, for example, it can be 0.95 ≤ a ≤ 1.2.
[0027] The smaller the cobalt ratio x, the easier it is for the composite oxide to become (deactivated) a crystal structure that is difficult to reversibly absorb and release lithium ions through repeated charge and discharge. In particular, when x≤0.02, the deactivation of the composite oxide is significant, and in order to stabilize the crystal structure, the necessity of replacing Co with Mn becomes high. Moreover, if Co is replaced with Mn, the problem of reducing the above-mentioned capacity retention rate occurs when a chain carboxylate is used as a solvent for the electrolyte. In this case, adding a cyclic compound is effective.
[0028] The atomic ratio of Mn in the second metal X can be 0.02 or more and 0.05 or less (0.02≤y≤0.05). If y≥0.02, it is easy to stabilize the structure of the positive electrode active material when the Co ratio x in the composite oxide is 0.02 or less. On the other hand, if y≤0.05, it is also easy to suppress the reduction of the capacity retention rate when the electrolyte contains a chain carboxylate by adding a cyclic compound.
[0029] Next, the nonaqueous electrolyte secondary battery according to the embodiment of the present disclosure is described in detail. The nonaqueous electrolyte secondary battery includes, for example, the following negative electrode, positive electrode, and electrolyte solution.
[0030] [negative electrode]
[0031] The negative electrode, for example, comprises: a negative electrode current collector; and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed as follows: a negative electrode slurry in which a negative electrode mixture is dispersed in a dispersion medium is applied to the surface of the negative electrode current collector and dried, thereby forming the negative electrode current collector. The dried coating film can be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.
[0032] The negative electrode mixture contains a negative electrode active material as an essential component and may contain a binder, a conductive agent, a thickener, etc. as optional components. The negative electrode active material includes: a material that electrochemically absorbs and releases lithium ions. As a material that electrochemically absorbs and releases lithium ions, carbon materials, Si-containing materials, etc. can be used. As Si-containing materials, silicon oxide (SiO x : 0.5≤x≤1.5), a composite material containing a silicate phase and silicon particles dispersed in the silicate phase (LSX), etc.
[0033] As carbon materials, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material with a graphite-type crystal structure, including natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon material can be used alone or in combination of two or more.
[0034] As the negative electrode current collector, a metal foil, a mesh, a net, a punched sheet, etc. are used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified.
[0035] [Positive electrode]
[0036] The positive electrode includes, for example: a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed as follows: by applying a positive electrode paste in which a positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it, it can be formed. The dried coating film can be calendered as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.
[0037] The positive electrode mixture contains a positive electrode active material as an essential component and can contain a binder, a conductive agent, etc. as optional components. The positive electrode active material contains a material that electrochemically occludes and releases lithium ions. In the positive electrode active material, a composite oxide having the same layered rock salt structure as LiCoO and obtained by substituting at least a part of Co with Ni, Al, and Mn can be used. The composite oxide can be, for example, the lithium-containing composite oxide represented by the above formula LiNi_xCo_yMn_zO_2 (where 0 ≤ x ≤ 0.02, 0 < y ≤ 0.05, 0 < z ≤ 0.1). In the above chemical formula, M can contain Al. The Co ratio can be substantially zero. That is, the composite oxide can be a LiNi_xMn_zO_2 (where 0 < y ≤ 0.05, 0 < z ≤ 0.1) that is substantially free of Co. 2 Similarly, a layered rock salt structure, and a composite oxide obtained by substituting at least a part of Co with Ni, Al, and Mn. The composite oxide can be, for example, the above-mentioned Li a Ni 1-x-y-z Co x Mn y M 1 z O 2 (where 0 ≤ x ≤ 0.02, 0 < y ≤ 0.05, 0 < z ≤ 0.1). In the above chemical formula, M 1 can contain Al. The Co ratio can be substantially zero. That is, the composite oxide can be a Li a Ni 1-y-z Mn y M 1 z O 2 (where 0 < y ≤ 0.05, 0 < z ≤ 0.1).
[0038] In terms of obtaining high capacity, the atomic ratio of Ni among the metals other than lithium can be 0.8 or more and less than 1 (0 < x + y + z ≤ 0.2), or can be 0.9 or more and less than 1 (0 < x + y + z ≤ 0.1). The atomic ratio of Ni can be 0.8 or more and 0.98 or less (0.02 ≤ x + y + z ≤ 0.2), or can be 0.9 or more and 0.98 or less (0.02 ≤ x + y + z ≤ 0.1).
[0039] Element M 1Other elements other than Co, Ni, Al and Mn may be contained. Examples of other elements include at least one selected from the group consisting of Na, Mg, Sc, Y, Fe, Cu, Zn, Cr, Pb, Sb and B.
[0040] As the positive electrode current collector, for example, metal foil is used, and examples of the material include stainless steel, aluminum, aluminum alloy, titanium, and the like.
[0041] As the binder of each electrode, resin materials such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polyacrylic acid salts (such as lithium polyacrylate), polymethyl acrylate, and ethylene-acrylic acid copolymers; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. These can be used alone or in combination of two or more.
[0042] Examples of the conductive agent include carbon blacks such as acetylene black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; organic conductive materials such as phenylene derivatives, etc. These may be used alone or in combination of two or more.
[0043] Examples of thickeners include carboxymethyl cellulose (CMC) and modified products thereof (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.); saponified products of polymers having vinyl acetate units such as polyvinyl alcohol; polyethers (polyalkylene oxides such as polyethylene oxide), etc. These may be used alone or in combination of two or more.
[0044] The dispersion medium is not particularly limited, and examples thereof include water, alcohol, and N-methyl-2-pyrrolidone (NMP).
[0045] [Electrolyte]
[0046] The electrolyte generally comprises: a solvent, a solute dissolved in the solvent, and an additive. The solute is an electrolyte salt that undergoes ion dissociation in the electrolyte, and may comprise a lithium salt. The electrolyte may comprise various additives. In the electrolyte, the total amount of the lithium salt and the solvent preferably accounts for more than 90% by mass of the electrolyte, and more preferably accounts for more than 95% by mass.
[0047] The solvent refers to: cyclic carbonate, cyclic carboxylic acid ester, chain carbonate and chain carboxylic acid ester, and electrolyte components that are liquid at 25°C and contain 3% by mass or more in the electrolyte. One or more solvents can be used in any combination. Components other than the solvent and the solute are additives, and cyclic compounds can be classified as additives.
[0048] Examples of the cyclic carbonate include propylene carbonate (PC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and vinylethylene carbonate (VEC).
[0049] Examples of the chain carbonate include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC).
[0050] Examples of the cyclic carboxylic acid ester include γ-butyrolactone (GBL) and γ-valerolactone (GVL).
[0051] The solvent contains a chain carboxylic acid ester having 2 to 4 carbon atoms. Examples of such chain carboxylic acid esters include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, and methyl propionate. Among them, methyl acetate has low viscosity and high stability, and can improve the low-temperature characteristics of the battery. The content of the above-mentioned chain carboxylic acid ester in the electrolyte is preferably 10% by volume or more and 80% by volume or less, and more preferably 20% by volume or more and 45% by volume or less. In this case, the viscosity of the electrolyte can be sufficiently reduced, and the cycle characteristics can be easily improved.
[0052] The solvent may further contain chain carboxylates other than those described above (ie, chain carboxylates having 5 or more carbon atoms).
[0053] In addition, even when the content of a polymer that is solid alone at 25° C. in the electrolyte is 3% by mass or more, the polymer is not contained in the electrolyte components. Such a polymer functions as a matrix for gelling the electrolyte.
[0054] Examples of the additive include carboxylic acids, alcohols, 1,3-propane sultone, toluene sulfonate, cyclohexylbenzene, biphenyl, diphenyl ether, and fluorobenzene, in addition to the above-mentioned cyclic compounds.
[0055] The electrolyte may contain other salts in addition to the above-mentioned lithium salts. Examples of other salts include LiClO 4 、LiAlCl 4 , LiB 10 Cl 10 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiCF 3 SO 3 、LiCF3 CO 2 、LiN(CF 3 SO 2 ) 2 、LiN(CF 3 SO 2 )(C 4 F 9 SO 2 )、LiN(C 2 F 5 SO 2 ) 2 , LiCl, LiBr, LiI, etc. One or more lithium salts may be used in any combination.
[0056] [Separator]
[0057] It is desirable to sandwich the separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, microporous films, woven fabrics, non-woven fabrics, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.
[0058] As an example of the structure of a non-aqueous electrolyte secondary battery, an electrode group in which a positive electrode and a negative electrode are wound with a separator and a non-aqueous electrolyte is contained in an outer shell can be cited. Alternatively, an electrode group in other forms such as a stacked electrode group in which a positive electrode and a negative electrode are stacked with a separator can be used instead of a wound electrode group. The non-aqueous electrolyte secondary battery can be, for example, in any form such as a cylindrical type, a square type, a coin type, a button type, and a laminated type.
[0059] Figure 1 This is a schematic perspective view in which a part of the nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is cut away.
[0060] The secondary battery 100 is a wound type battery including a wound electrode group 40 and a non-aqueous electrolyte (not shown). The wound electrode group 40 includes a strip-shaped positive electrode 10, a strip-shaped negative electrode 20, and a separator 30. A positive electrode lead 13 is connected to the positive electrode 10, and a negative electrode lead 23 is connected to the negative electrode 20.
[0061] One end of the positive lead 13 in the longitudinal direction is connected to the positive electrode 10, and the other end is connected to the sealing plate 90. The sealing plate 90 has a positive terminal 15. One end of the negative lead 23 is connected to the negative electrode 20, and the other end is connected to the bottom of the battery case 70 which serves as the negative terminal. The battery case 70 is a bottomed cylindrical battery can, one end of which is open in the longitudinal direction, and the bottom of the other end serves as the negative terminal. The battery case (battery can) 70 is made of metal, for example, iron. The inner surface of the iron battery case 70 is usually nickel-plated. An upper insulating ring 80 and a lower insulating ring 60 made of resin are respectively arranged above and below the wound electrode group 40.
[0062] In the example, a cylindrical non-aqueous electrolyte secondary battery with a wound electrode group is described, but it is not limited to this case, and this embodiment can be applied. The structure of the non-aqueous electrolyte secondary battery can be cylindrical, coin-shaped, button-shaped, etc. with a metal battery case, or a laminated battery with a laminated body of a barrier layer and a resin sheet, that is, a laminated sheet battery case. The shape of the electrode group is not particularly limited, and can be a laminated type.
[0063] Hereinafter, the disclosure will be specifically described based on Examples and Comparative Examples, but the disclosure is not limited to the following Examples.
[0064] <Example 1>
[0065] [Preparation of LSX]
[0066] Silicon dioxide and lithium carbonate were mixed so that the atomic ratio of Si / Li was 1.05, and the mixture was calcined in air at 950° C. for 10 hours to obtain a lithium carbonate having the formula: Li 2 Si 2 O 5 The obtained lithium silicate was pulverized so that the average particle size became 10 μm.
[0067] The average particle size of lithium silicate (Li 2 Si 2 O 5 ) and raw silicon (3N, average particle size 10 μm) were mixed at a mass ratio of 45:55. The mixture was filled into a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was pulverized at 200 rpm in an inert atmosphere for 50 hours.
[0068] Next, the powdered mixture was taken out in an inert atmosphere, and calcined at 800° C. for 4 hours in the inert atmosphere while applying pressure with a hot press, thereby obtaining a sintered body (LSX) of the mixture.
[0069] After that, LSX was crushed and passed through a 40 μm sieve, and the obtained LSX particles were mixed with coal tar (MCP250 manufactured by JFE Chemical Co., Ltd.), and the mixture was calcined at 800° C. in an inert atmosphere to cover the surface of the LSX particles with conductive carbon to form a conductive layer. The covering amount of the conductive layer was set to 5% by mass relative to the total mass of the LSX particles and the conductive layer. Then, using a sieve, LSX particles having an average particle size of 5 μm with a conductive layer were obtained.
[0070] [Production of negative electrode]
[0071] LSX particles with a conductive layer were mixed with graphite at a mass ratio of 3:97 and used as a negative electrode active material. The negative electrode active material was mixed with lithium polyacrylate and styrene-butadiene rubber (SBR) at a mass ratio of 97.5:1:1.5, and after adding water, it was stirred with a mixer (TKHIVIS MIX manufactured by Primix Corporation) to prepare a negative electrode slurry. Next, the negative electrode slurry was applied to the surface of the copper foil, and the coating was dried and rolled to form a negative electrode mixture layer on both sides of the copper foil.
[0072] [Production of positive electrode]
[0073] The lithium-containing composite oxide (LiNi 0.9 Co 0.02 Al 0.03 Mn 0.05 O 2 ), acetylene black, polyvinylidene fluoride, and N-methyl-2-pyrrolidone (NMP) are mixed in a predetermined mass ratio to prepare a positive electrode slurry. Next, the positive electrode slurry is applied to the surface of an aluminum foil as a positive electrode current collector, and the coating is dried and then rolled to form a positive electrode mixture layer on both sides of the aluminum foil.
[0074] [Preparation of non-aqueous electrolyte]
[0075] LiPF as a lithium salt was added to a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and methyl acetate (MA) in a volume ratio of 20:60:20. 6 , and 1,4-dioxane to prepare a non-aqueous electrolyte. LiPF in a non-aqueous electrolyte 6 The concentration of dioxane was set to 1.0 mol / liter. The content of dioxane was set to 1 mass % based on the total mass of the non-aqueous electrolyte.
[0076] [Fabrication of non-aqueous electrolyte secondary battery]
[0077] The electrode group was prepared by installing a tab on each electrode, and winding the positive electrode and the negative electrode in a spiral shape with the lead wire located at the outermost periphery through a separator. The electrode group was inserted into a metal battery can, vacuum dried at 105°C for 2 hours, and then injected with a nonaqueous electrolyte solution. The opening of the battery can was sealed to obtain a nonaqueous electrolyte secondary battery A1.
[0078] <Comparative Example 1>
[0079] In the preparation of the non-aqueous electrolyte, 1,4-dioxane was not added.
[0080] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except for the above, thereby obtaining Battery B1.
[0081] <Comparative Example 2>
[0082] Using lithium-containing composite oxide (LiNi 0.9 Co 0.07 Al 0.03 O 2 ) as the positive electrode active material.
[0083] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except for the above, thereby obtaining Battery B2.
[0084] <Comparative Example 3>
[0085] In the preparation of the non-aqueous electrolyte, 1,4-dioxane was not added.
[0086] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 2 except for the above, thereby obtaining Battery B3.
[0087] <Comparative Example 4>
[0088] In the preparation of the non-aqueous electrolyte, a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 20:80 was used.
[0089] In addition, 1,4-dioxane was not added.
[0090] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 2 except for the above, thereby obtaining Battery B4.
[0091] <Example 2>
[0092] In the preparation of the positive electrode, the lithium-containing composite oxide (LiNi 0.9 Al 0.05 Mn 0.05 O 2 ) is mixed with acetylene black, polyvinylidene fluoride and N-methyl-2-pyrrolidone (NMP) in a predetermined mass ratio to prepare a positive electrode slurry. Next, the positive electrode slurry is applied to the surface of an aluminum foil as a positive electrode current collector, and the coating is dried and rolled to form a positive electrode mixture layer on both sides of the aluminum foil.
[0093] The electrode group was prepared by installing a tab on each electrode, winding the positive electrode and the negative electrode in a spiral shape with the lead wire located at the outermost periphery through a separator. The electrode group was inserted into an outer casing made of an aluminum laminate film, vacuum dried at 105°C for 2 hours, and then injected with a non-aqueous electrolyte to seal the opening of the laminated outer casing.
[0094] Except for this, a nonaqueous electrolyte secondary battery A2 was obtained in the same manner as in Example 1.
[0095] <Comparative Example 5>
[0096] In the preparation of the non-aqueous electrolyte, 1,4-dioxane was not added.
[0097] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 2 except for the above, thereby obtaining Battery B5.
[0098] <Comparative Example 6>
[0099] In the preparation of the non-aqueous electrolyte, a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 20:80 was used.
[0100] In addition, 1,4-dioxane was not added.
[0101] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 2 except for the above, thereby obtaining Battery B6.
[0102] <Comparative Example 7>
[0103] Using lithium-containing composite oxide (LiNi 0.9 Co 0.07 Al 0.03 O 2 ) as the positive electrode active material.
[0104] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 2 except for the above, thereby obtaining a battery B7.
[0105] <Comparative Example 8>
[0106] In the preparation of the non-aqueous electrolyte, 1,4-dioxane was not added.
[0107] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 7 except for the above, thereby obtaining Battery B8.
[0108] <Comparative Example 9>
[0109] In the preparation of the non-aqueous electrolyte, a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 20:80 was used.
[0110] In addition, 1,4-dioxane was not added.
[0111] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 7 except for the above, thereby obtaining Battery B9.
[0112] [evaluate]
[0113] (Initial charge and discharge)
[0114] Each completed battery was placed in an environment of 45°C and charged at a constant current of 0.3 It until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.02 It. Thereafter, the battery was discharged at a constant current of 0.5 It until the voltage reached 2.5 V, and the initial discharge capacity C0 was obtained.
[0115] (DCIR measurement)
[0116] After the initial charge and discharge test, each battery was placed in an environment of 45°C and charged at a constant current of 0.3 It until the voltage reached 4.2 V. Then, it was charged at a constant voltage of 4.2 V until the current reached 0.02 It. After that, it was paused for 2 hours and discharged at a current of 0.5 It for 10 seconds. The resistance value was calculated from the voltage drop before and after, and was taken as the initial DCIR when SOC = 100%.
[0117] (Capacity maintenance rate)
[0118] The pause period between charge and discharge was set to 10 minutes, and charge and discharge were repeated under the above charge and discharge conditions at 45°C to obtain the discharge capacity C1 at the 300th cycle. The ratio of the discharge capacity C1 to the initial discharge capacity C0 (R1=C1 / C0) was evaluated as the capacity retention rate.
[0119] Table 1 shows the evaluation results of the capacity retention rate R1 and initial DCIR in batteries A1, B1 to B4. Table 1 also shows the presence or absence of methyl acetate (MA) and 1,4-dioxane (1,4-DOX) in the positive electrode active material and electrolyte used in each battery (the content ratio if included). The positive electrodes of batteries A1 and B1 contain 2% Co and 5% Mn, and the positive electrodes of batteries B2 to B4 contain 7% Co and no Mn.
[0120] Compared with battery B4, the initial DCIR of batteries B2 and B3 is lower. This is based on the effect of replacing part of the electrolyte solvent with low-viscosity methyl acetate. In fact, from the comparison of batteries A2, B5 and battery B6 in Table 2 described later, and the comparison of batteries B7, B8 and battery B9, it is also speculated that the effect of methyl acetate replacement is not dependent on the positive electrode composition. Therefore, in order to reduce the initial DCIR, it is important to replace part of the electrolyte solvent with methyl acetate.
[0121] Batteries A1 and B1 have a lower content of Co in the positive electrode active material than batteries B2 to B4, and therefore are more advantageous than batteries B2 to B4 in terms of manufacturing cost. However, when comparing battery B1 with battery B3, battery B1, which uses a lithium-containing composite oxide containing 5 atomic % of Mn as the positive electrode active material, has a lower capacity retention rate than battery B3. The reason for this is that the use of a solvent containing methyl acetate in the electrolyte makes it easier for Mn in the composite oxide to dissolve.
[0122] On the other hand, in battery A1, by adding 1,4-dioxane (1,4-DOX) to the electrolyte, the decrease in capacity retention rate was suppressed compared to battery B1. As a result, in the positive electrode composition with a Co ratio as low as about 2%, by containing methyl acetate (MA) and 1,4-dioxane (1,4-DOX), the initial DCIR can be reduced at low cost and a high capacity retention rate can be maintained.
[0123] In batteries B2 and B3, a lithium-containing composite oxide that does not contain Mn is used as the positive electrode active material. In this case, no significant difference in capacity retention rate is observed depending on the presence or absence of the addition of 1,4-dioxane (1,4-DOX). The suppression of the decrease in capacity retention rate caused by the addition of 1,4-dioxane (1,4-DOX) is an effect unique to NCAM.
[0124] Table 2 shows the evaluation results of the capacity retention rate R1 and initial DCIR in batteries A2, B5 to B9. As in Table 1, the presence or absence of methyl acetate (MA) and 1,4-dioxane (1,4-DOX) in the positive electrode active material and electrolyte used in each battery (the content ratio if contained). The positive electrodes of batteries A2 and B5 do not contain Co and contain 5% Mn, and the positive electrodes of batteries B7 to B9 contain 7% Co and do not contain Mn.
[0125] Comparison of the initial DCIR of batteries A2 and B5 to B9 shows that the inclusion of methyl acetate (MA) effectively reduces the initial DCIR.
[0126] However, the capacity retention rate of battery B5 containing methyl acetate (MA) was lower than that of battery B6 not containing methyl acetate (MA). This is probably because methyl acetate (MA) oxidized by charge and discharge cycles reacted with the positive electrode active material to cause Mn dissolution.
[0127] However, the capacity retention rate of battery A2 containing methyl acetate (MA) and further containing 1,4-dioxane (1,4-DOX) is higher than the capacity retention rate of battery B5 containing methyl acetate (MA) and not containing 1,4-dioxane (1,4-DOX). As in the case of the positive electrode containing Co2% and Mn5% shown in Table 1, in battery A2, by adding 1,4-dioxane (1,4-DOX) to the electrolyte, the decrease in capacity retention rate is suppressed compared with battery B5. That is, in the positive electrode without Co, the suppression of the decrease in capacity retention rate caused by the addition of 1,4-dioxane (1,4-DOX) is also confirmed.
[0128] The initial DCIR of battery A1 in Table 1 is slightly higher than that of battery B1. Similarly, the initial DCIR of battery A2 in Table 2 is slightly higher than that of battery B5. The reason is believed to be due to the film formed by 1,4-dioxane (1,4-DOX) during the initial charge and discharge. It is believed that the film formed by 1,4-dioxane (1,4-DOX) inhibits the dissolution of Mn.
[0129] [Table 1]
[0130]
[0131] [Table 2]
[0132]
[0133] Industrial Applicability
[0134] According to the present disclosure, a nonaqueous electrolyte secondary battery having excellent long-term cycle characteristics can be provided. The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.
[0135] Description of Reference Numerals
[0136] 10 Positive electrode
[0137] 13 Positive lead
[0138] 15 Positive terminal
[0139] 20 Negative electrode
[0140] 23 Negative lead
[0141] 30 Dividers
[0142] 40 Wound Electrode Group
[0143] 60 Lower insulation ring
[0144] 70 Battery housing
[0145] 80 Upper insulation ring
[0146] 90 Sealing plate
[0147] 100 Secondary batteries
Claims
1. A non-aqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode and an electrolyte, The positive electrode contains a composite oxide, The composite oxide has a layered rock salt structure and contains lithium as a first metal and a second metal X other than lithium, In the composite oxide, the second metal X includes Ni, Al, and Mn, and the atomic ratio of Ni in the metals other than lithium is greater than or equal to 0.8 and less than 1, The second metal X does not contain Co, or the atomic ratio Co / X of Co in the second metal X is less than 0.02, The electrolyte solution comprises: a chain carboxylic acid ester having 2 to 4 carbon atoms, and a cyclic compound having a ring structure consisting of 2 oxygen atoms and 3 to 5 carbon atoms, In the cyclic compound, the hydrogen atoms bonded to the carbon atoms constituting the ring structure are not substituted by a functional group or are substituted by a functional group, and the functional group is an alkyl group or an aromatic hydrocarbon group.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The atomic ratio Mn / X of Mn in the second metal X is greater than or equal to 0.02 and less than or equal to 0.
05.
3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The chain carboxylic acid ester is methyl acetate.
4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The cyclic compound is at least one selected from the group consisting of 1,2-dioxane, 1,3-dioxane, 1,4-dioxane, 2-benzyl-1,3-dioxane, 1,3-dioxolane, and 4-methyl-1,3-dioxolane.
5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The cyclic compound is 1,4-dioxane.
6. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The content of the cyclic compound is 0.5% by mass or more relative to the mass of the electrolyte.
7. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The content ratio of the chain carboxylic acid ester in the electrolyte is 10 volume % or more.
Citation Information
Patent Citations
Nonaqueous electrolyte and lithium cell adopting it
JP2004172120A
Lithium secondary battery
CN103250295A
Battery and electrolyte, and battery pack, electronic apparatus, electric vehicle, power storage device and electric power system
JP2013225388A